2019
DOI: 10.1016/j.jclinepi.2019.02.011
|View full text |Cite
|
Sign up to set email alerts
|

The selection of comparators for randomized controlled trials of health-related behavioral interventions: recommendations of an NIH expert panel

Abstract: Objectives: To provide recommendations for the selection of comparators for randomized controlled trials of health-related behavioral interventions. Study Design and Setting: The National Institutes of Health Office of Behavioral and Social Science Research (OBSSR) convened an expert panel to critically review the literature on control or comparison groups for behavioral trials and to develop strategies for improving comparator choices and for resolving controversies and disagreements about comparators. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
111
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(116 citation statements)
references
References 54 publications
0
111
0
Order By: Relevance
“…As outlined in our peer‐reviewed published systematic review protocol, we indicated in our PICO criteria that comparison groups may include attention control groups (ie, participants receive some attention such as education that is different from the intervention being tested). We included a range of comparison groups in our review as it is common in behavioral intervention trials to have some type of active comparison group . Based on our inclusion criteria, we feel it was appropriate to include the RESTORE trial in our systematic review.…”
Section: Summary Of Results From Studies Included In Review (N = 41)mentioning
confidence: 99%
“…As outlined in our peer‐reviewed published systematic review protocol, we indicated in our PICO criteria that comparison groups may include attention control groups (ie, participants receive some attention such as education that is different from the intervention being tested). We included a range of comparison groups in our review as it is common in behavioral intervention trials to have some type of active comparison group . Based on our inclusion criteria, we feel it was appropriate to include the RESTORE trial in our systematic review.…”
Section: Summary Of Results From Studies Included In Review (N = 41)mentioning
confidence: 99%
“…First, we wished to better account for contact time and expectancies for improvement across conditions for a future large‐scale trial. We also wanted to find a comparison that matched the mode of treatment delivery of LifeStories, which is video‐based and streamed over the internet, as the public is increasingly turning to the internet for health‐related information (Freedland et al, ). We further wanted to offer a novel intervention option that might be attractive to participants looking for an alternative approach to treating their depression.…”
Section: Methodsmentioning
confidence: 99%
“…As such, for pharmaceuticals only, one could think of classic RCTs as mechanistic science in real-world contexts. Within the social and behavioral sciences, the placebo is often not an appropriate control condition [ 136 ]. With new technologies and methods, the social and behavioral science can begin to localize effects in contexts to support both clinical decision-making and mechanistic science (see earlier discussion of HeartSteps microrandomization trial in the methods section, which illustrates this possibility).…”
Section: Opportunities For the Social And Behavioral Sciences Within mentioning
confidence: 99%